Pengaruh Pola Hidup Sehat pada Pasien Hipertensi dengan Pendekatan Social Cognitive Theory di Wilayah Kerja Puskesmas Tlogosadang - Amalia, Diah Amini (Future Science, 2024)
This study aims to analyze the influence of individual characteristics, personal factors and environmental factors on a healthy lifestyle in hypertensive patients. This research is a quantitative research with a descriptive verification design. The sampling technique was carried out by purposive sampling and the sample in this study totaled 300 people (hypertensive patients). The data used in this research is primary data collected through a questionnaire survey. Data analysis used path analysis, correlation coefficient, determination coefficient, and multiple linear regression tests. The research results obtained: 1) Individual characteristics consisting of: (age with p=0.114), (gender with p=0.000), (education with p=0.000), (family history with p=0.031), (perception of disease with p=0.000); 2) Personal factors consisting of: (self-efficacy with p=0.011), (self-regulation with p=0.000); 3) Environmental factors consisting of: (friend support with p=0.000), (family support with p=0.452), (health worker support with p=0.000); 4) The independent variables, namely individual characteristics, personal factors and environmental factors jointly affect the dependent variable, namely a healthy lifestyle in hypertensive patients (p=0.000; F=231.524; R2=88.9%).